PERKEMBANGAN PEREMPUAN MUHAMMADIYAH SULAWESI TENGGARA: (The Development of Muhammadiyah Women Southeast Sulawesi) - Mualimah, Mualimah (Uniqbu Journal of Social Sciences, 2022)
The purpose of this study is to find the development of Muhammadiyah women in Southeast Sulawesi, especially in Kendari city. The method used in this study is a qualitative research method with a historical approach. Data collection techniques are by 1. Field Research, 2. Source Criticism, 3. Interpretation and Historiography. The results of this study were started in the period 1968 -1971 Regional Leaders of Aisyiyah, South Sulawesi and Southeast Sulawesi were still joined, so it was abbreviated as PWA Sulawesi Tenggara, in this period Aisyiyah only formed Regional Leaders chaired by Hj. Andi Mappatombong After that Southeast Sulawesi separated from South Sulawesi so that the Regional Leader of Aisyiyah changed to the Regional Chair of Aisyiyah whose chairman was the same, namely Mrs. Hj. Andi Mappatombong. However, the Regional Chief of Aisyiyah had to suffer years of poverty due to political problems. Muhammadiyah began to re-establish the Regional Leadership of Aisyiyah Sulawesi Tenggara in 1987 and Intan Nirwana was elected as general chairman, but after serving for one year in 1988 she had to move to Makassar for professional reasons, then Tawaningsih was appointed to replace Intan's Nirwana in 1988 -1992. In the period of Mrs.Tawaningsih has not yet formed a PDA, because she is still busy carrying out cadre and other work programs, even though in that period the ABA TK was formed which was placed in the Pindayani Lepo-lepo housing for busy reasons so the ABA TK was not followed up. Then after the period of Mrs.Tawaningsih was over, egional deliberation was held again to appoint a general chairperson, and Tawaningsih's mother was re-elected but for reasons of her profession who at that time served as a judge in the religious court, so she had to resign as the general chairperson of PWA, then Mrs. Hajrah was elected Majid replaced Mrs. Tawaningsi in the period 1992 - 1996, then in the period 1996 - 2000 Fahima was chosen as the general chairperson. In the period of 2000 - 2005 Nurseha Gazali was elected as the general chairman to replace Fahima and in the 2005 - 2010 period Nurseha was re-elected. the next period, namely in 2010-2015, Marlina Gazali was chosen to replace Nurseha Gazali and continued in the next period in 2015 - 2020.